PENGEMBANGAN E-MODUL EKOLOGI BERBASIS ALEF EDUCATION UNTUK MENINGKATKAN KEPEDULIAN LINGKUNGAN PADA MATA PELAJARAN EKONOMI KELAS X DI SMA MUHAMMADIYAH 09 KUALUH HULU - Siti Jaisah; Dirgantara Wicaksono (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid advancement of digital technology has transformed learning into a more interactive and student-centered process. Environmental issues such as deforestation, river pollution, and natural resource exploitation require educational institutions to integrate environmental education into various subjects, including economics. This study aimed to develop an ecology e-module based on Alef Education to support economics learning. The study employed the Research and Development (R&D) method using the ADDIE model. Data were collected through observations, interviews, expert validation questionnaires, and student response questionnaires. The findings indicate that the developed e-module is highly feasible and practical for classroom use. The module enhances students' understanding of economics while fostering environmental awareness through contextual learning and interactive digital media. The developed product can support the implementation of the Merdeka Curriculum and promote sustainable learning.